The Effect of Product Display and Store Environment on Customer Loyalty through Customer Satisfaction - Pratiwi, Ariska Indah; Munawir, Munawir; Nurjannah, Nurjannah (Southeast Asia Journal of Business, Accounting, and Entrepreneurship, 2024)
This study aims to determine the effect of product display and store atmosphere on customer loyalty through customer satisfaction at Indomaret Latamacelling Palopo. The types of research used in this study are quantitative and qualitative. The data analysis technique used in this research is descriptive analysis and Structural Equation Model Partial Least Square (SEM-PLS). The results showed that product display had a significant effect on customer satisfaction, store atmosphere had a significant effect on customer satisfaction, product display had no significant effect on customer loyalty, store atmosphere had no significant effect on customer loyalty, customer satisfaction had a significant effect on customer loyalty, product display had a significant effect on customer loyalty through customer satisfaction, store atmosphere had a significant effect on customer loyalty through customer satisfaction. The implication of this study is that product display and store atmosphere have no effect on customer loyalty even though they are moderated by customer satisfaction.